Experimental substantiation of effectively administration of vinboron for analgesic activity increase of ibuprofen - F. V. Hladkykh; N. H. Stepaniuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Background. The increase of NSAIDs safety is current direction of modern pharmacology, because of so-called "class-specific" adverse reactions, which are common to this class, and the leading place among them is occupied by gastro-intestinal toxicity. In previous studies we have proved the ability of vinboron to neutralize ulcerogenic effect of ibuprofen (Hladkykh F.V. and al., 2014). The presence of the proven analgesic activity in the domestic antispasmodics (Stepaniuk H.I. and al., 2007) serves as the basis for research of vinboron action on analgesic aspect of ibuprofen pharmacotherapeutic effec.